Protectors or Predators for Albania? - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. This report was assigned the following topical and geographical subject headings by the RFE/RL: Foreign Relations Series: Eastern Europe; Country series: Albania The principal RFE/RL contributors to this report were: Zanga, Louis; Brown, James F.